Corporate Governance Professionals in Georgia: Institutional Evolution and the Emergence of a New Legal Profession - Giorgi Giguashvili (European Scientific Journal, ESJ, 2026)
This article examines the development of corporate governance professionals in Georgia as part of the country’s broader institutional transformation since the early post-Soviet transition. While corporate governance scholarship has traditionally focused on formal structures such as boards, shareholders, and regulatory frameworks, this study shifts attention to the individuals and functions responsible for sustaining governance processes within corporations. Using a qualitative institutional analysis, the article traces the evolution of governance-related roles through four stages: weak institutionalization in the 1990s, the emergence of internal governance coordination during the 2000s, the differentiation of governance roles under the influence of international capital markets between 2010 and 2022, and the increasing complexity of governance frameworks following the adoption of the new Law on Entrepreneurs in 2022. The analysis draws on legislative developments, regulatory frameworks, and corporate governance practices, with particular attention to the banking sector as a leading driver of governance innovation. The article argues that corporate governance professionals in Georgia have emerged gradually as a response to increasing legal and organizational complexity rather than through formal legal recognition. While governance roles have become more structured and visible within corporate practice, they do not yet constitute a fully institutionalized profession. Instead, they represent an emerging field shaped by institutional demand, regulatory development, and the need to translate legal frameworks into operational governance processes. The Georgian case demonstrates how professional roles can develop through institutional evolution and highlights the importance of governance-related expertise in supporting corporate decision-making. At the same time, the findings suggest that the future development of governance professionals remains contingent on broader structural factors, including market development, regulatory practice, and the continued maturation of corporate governance systems.